BL_GERICHTE 470 14 275 vom 22. Dezember 2014 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Strafrecht, vom 22. Dezember 2014 (470 14 275) - BL Gerichte (2014)
Untersuchungs- / Sicherheitshaft